2000
DOI: 10.1006/viro.2000.0476
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the HIV-1 LTR NF-κB-Proximal Sp Site III: Evidence for Cell Type-Specific Gene Regulation and Viral Replication

Abstract: It has been widely demonstrated that the human immunodeficiency virus type 1 (HIV-1) envelope, specifically the V3 loop of the gp120 spike, evolves to facilitate adaptation to different cellular populations within an infected host. Less energy has been directed at determining whether the viral promoter, designated the long terminal repeat (LTR), also exhibits this adaptive quality. Because of the unique nature of the cell populations infected during the course of HIV-1 infection, one might expect the opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 56 publications
4
50
0
Order By: Relevance
“…1B) (31). Importantly, experimental evidence is suggestive that the Sp1III site is functionally more important for the viral promoter than the other two (18,19,32). Given the biological significance of the centrally located Sp1III motif and the subtype-associated variations within this motif among HIV-1 subtypes, we asked if the heterologous Sp1III sequences derived from the other HIV-1 subtypes can substitute for the original Sp1III sequence in C-LTR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B) (31). Importantly, experimental evidence is suggestive that the Sp1III site is functionally more important for the viral promoter than the other two (18,19,32). Given the biological significance of the centrally located Sp1III motif and the subtype-associated variations within this motif among HIV-1 subtypes, we asked if the heterologous Sp1III sequences derived from the other HIV-1 subtypes can substitute for the original Sp1III sequence in C-LTR.…”
Section: Resultsmentioning
confidence: 99%
“…Of the three motifs, the Sp1III site plays a more deterministic role in gene expression from the LTR, as Sp1 protein binding at this site must physically interact with the p65 protein of NF-B recruited to the H-B site located immediately upstream (17). Thus, the Sp1III site critical for the regulation of gene expression for the viral promoter demonstrates subtype-specific sequence variations, and the influence of such variations has not been adequately examined (18,19). Third, in contrast to the large genetic variation of the Sp1 sites, the sequence context of the NF-B binding sites is invariable in the viral strains regardless of the copy number difference.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, there is redundancy and overlap in the TFBS function that ensures replication in several cellular environments. On the other hand, the LTR also contains sites that enhance replication in specific cellular environments (1,28,34,42,47,51). It seems likely that the subtype-specific variation in HIV-1 represents different adaptational solutions as a result of a changing and/or fluctuating environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, deletion of the LTR Sp binding sites or GC box array has been shown to dramatically reduce Tat transactivation [16]. In clinical samples derived from HIV-1-infected patients in years prior to or after the implementation of effective combination antiretroviral therapy(cART), specific single-nucleotide polymorphisms have been observed within the NF-κB-proximal Sp transcription factor binding sites that exhibit a very low affinity for their cognate factor and alter LTR-driven viral gene activation [17,18]. Specifically, these studies reported that LTR sequence variants within the Sp site III (5T; a C-to-T change at position 5 of the binding site) were prevalent during the course of HIV-1 infection and exhibit very low binding affinities for members of the Sp transcription factor family [19,20].…”
Section: Introductionmentioning
confidence: 99%